Foreign portfolio equity flows in selected Sub-Saharan Africa Countries: the underlying process, impact on stock market capitalisation, and policy options - Mbao, Francis Ziwele (Department of Finance and Tax, 2022)
The volatility of capital flows and their adverse impact on macroeconomic and financial variables is a major concern to policy makers, resulting in a debate on whether capital controls or financial (capital account) liberalisation is best suited to managing them. This study argues that a better understanding of the underlying process of the foreign capital flows, that is, whether they are a random walk, a persistent, or an anti-persistent series, is a critical but currently lacking element in informing this debate. Specifically for foreign portfolio equity flows, there may also be need to understand their dynamic impact on stock markets. The purpose of this study is therefore to determine the underlying process of foreign portfolio equity flows in the sub-Saharan Africa countries for which a sufficiently long data series is available (i.e., Kenya, Nigeria, South Africa, and Zambia); to establish the impact of these flows on the capitalisation of their stock markets; and draw conclusions on optimal policy choices based on this. Secondary monthly data, covering the period January 1994 to March 2019, is used, but with different sample periods for each country within that range. Structural break estimations are further undertaken to obtain more specific results. Fractal analysis is employed to estimate the Hurst parameter, a measure of the underlying process. This is aided by fractal signal classification, adopted from electronic and communication engineering and physiology, a novel approach in the analysis of capital flows, to avoid misinterpreting the estimated Hurst parameter. The correlation measure technique, another novelty in the analysis of foreign capital flows, is also used to further understand the underlying process of the flows. Bayesian techniques based on sign restrictions are employed in estimating the Calderon-Rossell model, a unique approach, to establish the impact of these flows on stock market capitalisation. The robustness of the results is tested with the Fry and Pagan Median target method. The results indicate that the underlying process of gross foreign portfolio equity inflows and outflows in the four sub-Saharan Africa countries are anti-persistent. Further, increases in market capitalisations owing to positive shocks to foreign portfolio equity inflows are greater than declines resulting from shocks to outflows. The policy implication of these results for the four SSA countries is that capital controls on foreign portfolio equity flows are redundant.